The development of highly potent and selective small molecule correctors of Z α1-antitrypsin misfolding. (1st June 2021) - Liddle, John; Pearce, Andrew C.; Arico-Muendel, Christopher; Belyanskaya, Svetlana; Brewster, Andrew; Brown, Murray; Chung, Chun-wa; Denis, Alexis; Dodic, Nerina; Dossang, Anthony; Eddershaw, Peter; Klimaszewska, Diana; et al.
Graphical abstract: Abstract: α1-antitrypsin deficiency is characterised by the misfolding and intracellular polymerisation of mutant α1-antitrypsin protein within the endoplasmic reticulum (ER) of hepatocytes. Small molecules that bind and stabilise Z α1 -antitrypsin were identified via a DNA-encoded library screen. A subsequent structure based optimisation led to a series of highly potent, selective and cellular active α1-antitrypsin correctors.